(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, general issues related to the organization of internal audit activities in the public sector and generalization of the results were considered, and proposals were developed for generalization of the results of internal audit activities in the public sector. Also, theoretical approaches to the organization of the internal audit service have been reflected.